Izrazi za sneg in smuči v slovenski smučarski terminologiji - Bokal, Ljudmila (Slavia Centralis, 2020)
The terms for snow and skis in Slovene ski terminology Snow and skis are the fundamental terms of skiing terminology. In the past a significant share of the terms in both concept groups thrived in dialects. From there they passed into the standard language, where they are now indispensable units of Slovenian skiing terminology. The vitality of this terminology is also evident in its responsiveness to new technological achievements (carving skis).